-21+3n=-8(n-7)

Simple and best practice solution for -21+3n=-8(n-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -21+3n=-8(n-7) equation:


Simplifying
-21 + 3n = -8(n + -7)

Reorder the terms:
-21 + 3n = -8(-7 + n)
-21 + 3n = (-7 * -8 + n * -8)
-21 + 3n = (56 + -8n)

Solving
-21 + 3n = 56 + -8n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '8n' to each side of the equation.
-21 + 3n + 8n = 56 + -8n + 8n

Combine like terms: 3n + 8n = 11n
-21 + 11n = 56 + -8n + 8n

Combine like terms: -8n + 8n = 0
-21 + 11n = 56 + 0
-21 + 11n = 56

Add '21' to each side of the equation.
-21 + 21 + 11n = 56 + 21

Combine like terms: -21 + 21 = 0
0 + 11n = 56 + 21
11n = 56 + 21

Combine like terms: 56 + 21 = 77
11n = 77

Divide each side by '11'.
n = 7

Simplifying
n = 7

See similar equations:

| 3.4x=18 | | 20s^2+26d+8=0 | | 3x+4(3+5x)=2(4x-3) | | 7x+9y=64 | | 30+n=5(-8n+6) | | 4x-6y=-24 | | x^2-x=-20 | | -5(5+3x)=11-6x | | 4x^2+7x-44=0 | | 4-2(2+5v)+7= | | -5p-7=-(3p-3)-4p | | 4y^2-81x^2=-162x+405 | | .2x+2.4-12=0 | | x-7+(-99)=581 | | x-29=83 | | 41(52+13)=x+10-17 | | -5x^3+20x^2+20x+80=0 | | 91n^1+49n=0 | | 63n^2+63n=0 | | 15(x-4)=-6-9 | | -7x+4(3-5)=0 | | 10+x-.33333333x=0 | | 10+x-.33333333=0 | | x^2-15x+10=0 | | 5=2.5-4x | | x^6+8x^3+7=0 | | -1.5x=5 | | (3x+7)*(-8x-7)= | | 2.5-4x=5 | | .4+4x=5 | | 3k+13=19k-8 | | x-9y=19 |

Equations solver categories